MODEL AND STRATEGY OF ADOLESCENT SELF-INJURY CRISIS INTERVENTION: AMETA-ANALYSIS - Zhensong, Lan (International Journal of Psychosocial Rehabilitation, 2020)
Self-harm and suicide behaviors get recognized as major public health concerns, and WHO has ranked the burden of self-inflicted injuries as the significant leading reasons for disability-adjusted life years. Adolescence is a stage of a heightened risk of suicide, interventions that can reduce suicidal risk need to be madeavailable to this age group who self-harm more often. Preventive measures that aid adolescents need to get instituted at the onset of adolescence and for peer groups since these young adults often ask for support from friends. The study aimed to review the models and strategies for interventions of NSSI in adolescents. All treatments studied-development individual cognitive-behavioral therapy and pharmacological interventions for young people were found to be similar to the typical interventions provided in the settings of treatment where the research was carried out. Additional interventions such as involvement of family members have also some evidence suggesting they may be effective.